The Influence of Work Motivation and Work Environment on Employee Performance at Trapo Indonesia - Putri Khairunnisa; Setyo Riyanto (Syntax Corporation Indonesia, 2020)
The impact of work inspiration and work environment on work execution is very important, and some theoretical and fact assessments in several companies also show work motivation and a supportive environment that provides a very large increase in employee performance, plus in this “NEW NORMAL” period many companies make breakthroughs in running its business once again so that the company can survive in the midst of this crisis. Based on these conditions, the quality of performance and motivation in a company needs to be improved by formulating a new policy in the work system in the company so that it can pass through times like this, which is a new program or procedure in the system to improve employee performance in a company. The method used in this study is the procedure for approaching employees, research that emphasizes the basic principles of work motivation and the environment which seeks to create a new work environment that is more developed in situations like this. The theory outlined below will greatly assist companies, especially Trapo Indonesia, in evaluating and updating inspiration and work environment governance that can have a positive effect on the company and can moreover progress representative execution even better.